गोण्ड जनजातीय गीत - Kushram, Roop Singh (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2003)
The book contains a collection of folk songs of the Gond tribe.
Gond Janjatiya Geet
Keywords: Gondi; Folk Culture; Gondi; Hindi; Gondi